Community perceptions on climate change effect and household food security in Karatu district, Tanzania - Kyusilu, Jacqueline (Mzumbe University, 2023)
A Dissertation Submitted in Partial Fulfilment of the Requirements for the Award of the Degree of Master of Science in Environmental Management (MSc EM) of Mzumbe University